STRATEGI PENYIARAN ISLAM ADAT BASANDI SYARAK, SYARAK BASANDI KITABULLAH - Mega Puspita; Khairul Umami (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2023)
This article is about the Minangkabau Muslim community who use the syarak basandi custom. Syarak basandi Kitabullah is a traditional philosophy. This philosophy is a philosophy of life that is held by the Minangkabau people, they make Islam a basis/guideline for behavior in social life. Recently, a new law was issued which explains customary philosophy in Article 5 Letter c, namely Law Number 17 of 2022 concerning the Province of West Sumatra. The method in this research is juridical-normative. The findings in the study of the West Sumatra Law have many interpretations, firstly, adat basandi syarak, syara' with the joint of the Kitabullah which is intended for all communities of Mutuka Nagari in West Sumatra Province. Second, the custom of basandi syara', syara' based on the book of Allah is intended for the Minangkabau community. Third, this law has an impact on the Mentawai people who do not accept this provision, because they feel they have a different culture and characteristics from Minangkabau. This West Sumatra Law is not a sharia regional regulation like Aceh but only limited to customs that are strengthened and recognized by the country of existence and are still based on the Unitary State of the Republic of Indonesia.